Qumran Cave 1 revisited : texts from Cave 1 sixty years after their discovery : proceedings of the Sixth Meeting of the IOQS in Ljubljana - Falk, Daniel K. (Studies on the Texts of the Desert of Judah, 2010)
This volume contains a selection of the papers presented at the sixth meeting of the International Organization for Qumran Studies, held in 2007 in Ljubljana, Slovenia, on the topic "Qumran Cave 1 Revisited: Reconsidering the Cave 1 Texts Sixty Years after Their Discovery." While the opening paper assesses theories about the character of Qumran Cave 1 in relation to the other Qumran caves, all other papers discuss texts from Cave 1, in particular six of the seven large scrolls found there in 1947: the two Isaiah scrolls, the Rule of the Community, the War Scroll, the Thanksgivings Scroll, and the Genesis Apocryphon. Many papers revisit those texts in light of the corresponding versions found in Cave 4.